Tracking Changes in Students’ Online Self-Regulated Learning Behaviors and Achievement Goals Using Trace Clustering and Process Mining - Taub, Michelle; Banzon, Allison M.; Zhang, Tom; Chen, Zhongzhou (Frontiers in Psychology, 2022)
Success in online and blended courses requires engaging in self-regulated learning (SRL), especially for challenging STEM disciplines such as physics. This involves students planning how they will navigate course assignments and activities, setting goals for completion, monitoring their progress and content understanding, and reflecting on how they completed each assignment. Based on Winne & Hadwin’s COPES model, SRL is a series of events that temporally unfold during learning, impacted by changing internal and external factors such as goal orientation and content difficulty. Thus, as goal orientation and content difficulty change throughout a course, so might students’ use of SRL processes. This paper studies how students' SRL behavior and achievement-goal orientation changes over time in a large (N = 250) college introductory level physics course taught online. Students’ achievement-goal orientation was measured by repeated administration of the achievement goals questionnaire–revised (AGQ-R). Students’ SRL behavior was measured by analyzing their clickstream event traces interacting with online learning modules via a combination of trace-clustering and process-mining. Event traces were first divided into groups similar in nature using agglomerative clustering, with similarity between traces determined based on a set of derived characteristics most reflective of students' SRL processes. We then generated causal nets for each cluster of traces via process mining and interpreted the underlying behavior and strategy of each causal net according to the COPES SRL framework. We then measured the frequency at which students adopted each causal net, and assessed whether the adoption of different causal nets were associated with responses to the AGQ-R. By repeating the analysis for three sets of online learning modules assigned at the beginning, middle and end of the semester, we examined how the frequency of each causal net changed over time, and how the change correlated with changes to the AGQ-R responses. Results have implications for measuring the temporal nature of SRL during online learning, as well as the factors impacting the use of SRL processes in an online physics course. Results also provide guidance for developing online instructional materials that foster effective SRL for students with different motivational profiles.